Enhancing Firm Value through ESG Disclosure: Analyzing Non-Banking Companies in the LQ45 Index - Chairul, Muhammad; Prasetyo, Aries Heru (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2024)
The fourth industrial revolution has had a significant impact on economic progress, triggering intense competition between companies to achieve their goals. One effective strategy to increase company value is to adopt sustainable financial reporting that prioritizes economic stability and inclusiveness. The aim of this research is to investigate the impact of implementing Environmental Social and social Governance (ESG) reporting on the value of non-banking companies listed on the Indonesia Stock Exchange (BEI) in the LQ 45 index during the 2021-2023 period. Using descriptive, verification and regression analysis techniques, this research shows the influence of ESG-independent variables on company value. Data was collected from the annual reports of 23 non-banking companies included in the LQ 45 index. The results of this research are that environmental and social coverage has a significant positive influence on company value, while governance coverage does not show a significant influence. In addition, increasing sales as a controlling factor does not have a significant impact on company value. In conclusion, ESG reporting can increase a company's attractiveness to investors, with environmental and social factors being key. This research suggests increasing the number and longer sample time period for future research to obtain more comprehensive results